Analysis of multiple scattering contributions in electron-impact ionization of molecular hydrogen. (29th September 2017) - Ren, Xueguang; Hossen, Khokon; Wang, Enliang; Pindzola, M S; Dorn, Alexander; Colgan, James
Abstract: We report a combined experimental and theoretical study on the low-energy ( E 0 = 31.5 eV) electron-impact ionization of molecular hydrogen (H2 ). Triple differential cross sections are measured for a range of fixed emission angles of one outgoing electron between θ 1 = − 70 ° and −130° covering the full 4 π solid angle of the second electron. The energy sharing of the outgoing electrons varies from symmetric ( E 1 = E 2 = 8 eV) to highly asymmetric ( E 1 = 1 eV and E 2 = 15 eV). In addition to the binary and recoil lobes, a structure is observed perpendicular to the incoming beam direction which is due to multiple scattering of the projectile inside the molecular potential. The absolutely normalized experimental cross sections are compared with results from the time-dependent close-coupling (TDCC) calculations. Molecular alignment dependent TDCC results demonstrate that these structures are only present if the molecule axis is lying in the scattering plane.